Adverse childhood experiences among children placed in and adopted from foster care: Evidence from a nationally representative survey. (February 2017) - Turney, Kristin; Wildeman, Christopher
Abstract: Despite good reason to believe that children in foster care are disproportionately exposed to adverse childhood experiences (ACEs), relatively little research considers exposure to ACEs among this group of vulnerable children. In this article, we use data from the 2011–2012 National Survey of Children's Health (NSCH), a nationally representative sample of non-institutionalized children ages 0–17 in the United States, to estimate the association between foster care placement and exposure to an array of ACEs. In adjusted logistic regression models, we find that children placed in foster care or adopted from foster care, compared to their counterparts, were more likely to experience parental divorce or separation, parental death, parental incarceration, parental abuse, violence exposure, household member mental illness, and household member substance abuse. These children were also more likely to experience ACEs than children across different thresholds of socioeconomic disadvantage (e.g., children in households with incomes below the poverty line) and across different family structures (e.g., children in single-mother families). These results advance our understanding of how children in foster care, an already vulnerable population, are disproportionately exposed to ACEs. This exposure, given the link between ACEs and health, may have implications for children's health and wellbeing throughout the life course.